Perspektif Sosio-Antropologi Tentang Fenomena Mahar Dalam Perkawinan - Mashanda, Vebya Yuwa Ayu; Amalia Putri, Nadia Febri; Amelia, Nadila Zahro (Maliki Interdisciplinary Journal, 2025)
According to some scholars, a dowry is obligatory, a man is obliged to give a dowry to a woman when entering into a marriage, a dowry is a symbol of a woman's honor because she has shown her dignity as a future wife who is respected in a marriage bond. The dowry is a symbol of a man's love and affection for the woman he proposes to marry. In some tribes, the size of the dowry depends on their social status, whereas in Islam the giving of the dowry must be adjusted to the man's economy. This research aims to find out the socio-anthropological perspective on the phenomenon of dowry in marriage. This research uses library research where the data sources are obtained from documents and libraries using normative means, namely relying on laws and norms.